2007
DOI: 10.2332/allergolint.o-07-489
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Eosinophil-derived Neurotoxin Concentrations in Patients with Atopic Dermatitis: A Useful Clinical Marker for Disease Activity

Abstract: The urinary EDN concentration in patients with atopic dermatitis is a useful clinical marker for monitoring disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…The obvious advantage of non-invasiveness with urinary proteomics is tempered by the increased variability arising due to intra-individual and inter-individual changes in urine volume, pH, and other urine constituents [31,32]. The approach of creatinine correction for urine levels of biomarkers is routinely used in urine proteomics [33][34][35] and it was considered valid for studies involving measurement of urine chemokines that are believed to be passively released into urine from urothelium during the storage phase of micturition. Since passive secretion of chemokines from the bladder to the stored urine is independent of the urine flow rate downstream of kidney, creatinine adjustment together with volume of urine voided at the time of collection could be a suitable alternative method for correcting the dilution status of urine.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious advantage of non-invasiveness with urinary proteomics is tempered by the increased variability arising due to intra-individual and inter-individual changes in urine volume, pH, and other urine constituents [31,32]. The approach of creatinine correction for urine levels of biomarkers is routinely used in urine proteomics [33][34][35] and it was considered valid for studies involving measurement of urine chemokines that are believed to be passively released into urine from urothelium during the storage phase of micturition. Since passive secretion of chemokines from the bladder to the stored urine is independent of the urine flow rate downstream of kidney, creatinine adjustment together with volume of urine voided at the time of collection could be a suitable alternative method for correcting the dilution status of urine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, granular proteins can be identified in the blood and urine of AD patients, and they usually correlate with disease activity [126][127][128][129]. Eosinophil-specific granule proteins, including MBP, ECP, and EDN/EPX, are elevated in the peripheral blood of most AD patients and appear to correlate with disease activity [115].…”
Section: Eosinophilia In Admentioning
confidence: 97%
“…Studies have shown the successful use of serum ECP [130], MBP [131], and EDN [132] as sensitive measures for monitoring disease activity in AD. Furthermore, the urine concentration of EDN/EPX has been shown to be an indirect measure of inflammatory activity in AD [127][128][129]133]. More specific studies have shown that levels of serum EDN are even Fig.…”
Section: Eosinophilia In Admentioning
confidence: 98%
“…Despite this, ECP remains the eosinophil degranulation protein used most widely in clinical practice15). As a monitoring tool, EDN has had good results10,11,16,17). In Taniuchi et al's study11) involving atopic dermatitis patients, the serum EDN levels in mild, moderate, and severe groups were significantly higher than that in the control group ( P <0.01, P <0.05, and P <0.05, respectively).…”
Section: Eosinophil Degranulation Proteinsmentioning
confidence: 99%